How can an agri-environmental scheme be designed for farmland bird protection, and what does it mean for the CAP 2023–2027? - Buschmann, Christoph; Narjes, Manuel; Röder, Norbert (Elsevier, 2023)
Biodiversity loss is recognized as a major global threat. The European Commission has addressed this issue with vigour in its current strategy papers. Farmland birds, such as the lapwing (Vanellus vanellus), whose population has been rapidly declining in Germany, have been particularly affected. To date, the European Union has tried to tackle the problem of biodiversity loss mainly with voluntary agri-environmental schemes (AESs), which are financed by the European Agricultural Fund for Rural Development (EAFRD). However, only a small fraction of agricultural land is enrolled in such programs. We identify the possible drivers and inhibitors of farmers’ acceptance of a potential AES that, if introduced, could contribute to lapwing conservation. Our analysis is based on a discrete choice experiment conducted with 252 arable farmers in Germany. The results suggest that scheme attributes tied with EAFRD compliance, i.e., a minimum participation period of five years and the nature of the relevant sanctions regime, reduce farmers’ potential acceptance of the proposed AES. Furthermore, farmers and farm characteristics have an influence on preferences for specific AES attributes. Finally, this article outlines how the identified weaknesses of AES may be addressed in the new “Green Architecture” of the Common Agricultural Policy 2023–2027.